Jacqueline Kennedy Onassis a portrait of her private years - David, Lester (Carol Publishing Group Secaucus, 1994)
This revelatory, memorable book by the dean of America's Kennedy writers begins where the bestselling phenomenon A Woman Named Jackie left off, going even further into the life of Jacqueline Kennedy Onassis. Lester David evokes in fascinating detail what happened to Jackie after her marriage to Aristotle Onassis. When she died, after a determined battle with cancer, her passing brought forth an outpouring of grief and universal affection.; Here the author explores the life of a mature Jackie: a woman who associated little with the Kennedy clan while continuing to look after her children. Though she still owned John Kennedy's house in Hyannis Port, she never attended the traditional Kennedy get-togethers. And while she was fond of Ted Kennedy - remembering his kindness to her and how he fought for her inheritance rights after the death of Onassis - she disliked Ethel and had nothing to do with the younger Kennedy generation.; The book also focuses on what it was like being a book editor in the heart of Manhattan as one of the most recognizable women in history.; In addition, Jacqueline Kennedy Onassis: A Portrait of Her Private Years includes new revelations about her relationships with Jack Kennedy and Aristotle Onassis: despite claims to the contrary, Jackie had a deep interest in the political process, as well as domestic and foreign affairs, and helped counsel Jack on his schedule and campaign appearances; during his Senate years she would go over Jack's speeches, editing them carefully. He would approve her changes.; She also made suggestions on issues that Jack thought were excellent and which he adopted; after the assassination, her despondency was so severe that friends feared she might lose her mind or commit suicide; and the real reason Jackie married Onassis was not money. Rather, the murder of Bobby Kennedy again drove her to the edge of madness. Through the Onassis marriage she sought emotional security for herself and safety for her children. She said, "If they are killing Kennedys, my kids are number one targets.; I want to get out of this country."
Keywords: Onassis, Jacqueline Kennedy -- 1929-1994; Celebrities -- United States; Presidents' wives -- United States; Biography -- United States